2014
DOI: 10.4137/bbi.s15211
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Studies of Medicinal Compounds against Hepatitis C Capsid Protein from North India

Abstract: Hepatitis viral infection is a leading cause of chronic hepatitis, cirrhosis, and hepatocellular carcinoma (HCC). Over one million people are estimated to be persistently infected with hepatitis C virus (HCV) worldwide. As capsid core protein is the key element in spreading HCV; hence, it is considered to be the superlative target of antiviral compounds. Novel drug inhibitors of HCV are in need to complement or replace the current treatments such as pegylated interferon’s and ribavirin as they are partially bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…On the other hand, in silico studies have been carried out to evaluate naringenin activity on the HCV particle. Mathew et al[ 208 ] in 2014 reported a docking interaction study between the 3D structure of capsid core protein of HCV-genotype 3 (G3) (Q68867) and its subtypes 3b (Q68861) and 3g (Q68865) from north India and naringenin. The results indicated that the flavonoid exhibited five, seven and nine H-bond interactions within the core protein of HCV-G3, subtypes 3b and 3g, respectively.…”
Section: Antiviral Properties Of Naringeninmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in silico studies have been carried out to evaluate naringenin activity on the HCV particle. Mathew et al[ 208 ] in 2014 reported a docking interaction study between the 3D structure of capsid core protein of HCV-genotype 3 (G3) (Q68867) and its subtypes 3b (Q68861) and 3g (Q68865) from north India and naringenin. The results indicated that the flavonoid exhibited five, seven and nine H-bond interactions within the core protein of HCV-G3, subtypes 3b and 3g, respectively.…”
Section: Antiviral Properties Of Naringeninmentioning
confidence: 99%
“…In the case of HCV-3b, naringenin formed three H-bonds with TRP90, two with GLN86, and one with GLY84 and TRP93, with an interaction energy of -145.682 kcal/mole. Finally, the flavanone binds to HCV-3g through two H-bonds with TRP73 and GLY77 and individually with ASN85, TYR78 and TRP73 with an interaction energy of -159.483 kcal/mole[ 208 ]. These results suggest that naringenin binds to the core protein of three important HCV genotypes in India, especially to HCV-3 based on their interaction energies; this ability of naringenin to bind core protein could be involved in the inhibition of viral particle assembly that was previously reported.…”
Section: Antiviral Properties Of Naringeninmentioning
confidence: 99%
“…In these patients, local ablative therapies, including chemoembolization, potentially novel chemotherapeutic agents and radiofrequency ablation (RFA), may provide palliation and extend life. With the emergence of extremely effective direct-acting antivirals (DAAs) for hepatitis, 1 it is expected to reduce the incidence of hepatitis-related HCC. 3 Overall, a combination of virus-specific, environmental, immune-related factors and host genetics are likely to determine the progression and treatment of HCC.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…69 The antiviral activity of ladanein has been demonstrated effective against all HCV genotypes which lead to liver cancer. 1,70…”
Section: Ballotanigramentioning
confidence: 99%
See 1 more Smart Citation